Determining factors related to impaired spinal and hip mobility in patients with axial spondyloarthritis : longitudinal results from the DESIR cohort - Carvalho, Pedro D. (2021)
Copyright information: © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.